Climate drivers of seed production in Picea engelmannii and response to warming temperatures in the southern Rocky Mountains. (8th April 2016) - Buechling, Arne; Martin, Patrick H.; Canham, Charles D.; Shepperd, Wayne D.; Battaglia, Mike A.
Summary: Seed production by Picea engelmannii was monitored at 13 sites distributed across a ˜670 m elevation gradient for 40 years. Time series of annual seed output was investigated for evidence of masting behaviour and trends in seed abundance over time. We used regression models in a likelihood framework to examine climate effects on seed production for critical periods in the species' reproductive cycle. We rigorously evaluated the performance of two gridded climate data sets, PRISM and TopoWx, before using associated variables as predictors in the seed models. Seed production at these sites does not strictly conform to the classic masting concept. Seed abundance was highly variable over time and strongly synchronized among sites, but mast years could not be objectively identified due to intermediate levels of seed output. Model results indicate that climate conditions across multiple years cumulatively determine reproductive output. High seed rain is associated with elevated summer temperatures in the year that seeds are dispersed, low spring snowfall in the year preceding seed dispersal when buds are initiated, and reduced spring snowfall in a so‐called priming year two years prior to seed dispersal. Low spring precipitation putatively increases growing season length and resource accumulation in seed trees. Linear models identified significant positive trends in seed output over time. Anomalous aridity and summer warmth in the latter half of the study period were highly favourable for seed production and were associated with increases in seed abundance. Synthesis . The increases in seed output observed in this study may promote population fitness of P. engelmannii in the face of changing climate regimes and increasing frequencies of fire‐ and insect‐related tree mortality in the Rocky Mountains. Since this species lacks a persistent seed bank, re‐colonization of disturbed areas or dispersal to shifting habitats depends on adequate production of seed by surviving trees, which according to these analyses may be moderately enhanced by current climate trends. However, some evidence also indicates that increases in seed output will ultimately be constrained by threshold high temperatures in the seed maturation year. Abstract : The increases in seed output observed in this study may promote population fitness of P. engelmannii in the face of changing climate regimes and increasing frequencies of fire‐ and insect‐related tree mortality in the Rocky Mountains. Since this species lacks a persistent seed bank, re‐colonization of disturbed areas or dispersal to shifting habitats depends on adequate production of seed by surviving trees, which according to these analyses may be moderately enhanced by current climate trends. However, some evidence also indicates that increases in seed output will ultimately be constrained by threshold high temperatures in the seed maturation year.